Understanding the risks, links and consequences of climatic events, conflict and migration : perceptions from asylum seekers in Germany - Kohler, Christina Rita Laila (2019)
Tese (doutorado)—Universidade de Brasília, Centro de Desenvolvimento Sustentável, Programa de Pós-Graduação em Desenvolvimento Sustentável, 2019.